A Brief History of "Asphyxia". Issue 2 (June 2015) - Milroy, Christopher M.
The term "asphyxia" has been used in different ways for the last two centuries in forensic medicine. While it has come to mean deaths associated with the deprivation of oxygen, its literal meaning is absence of the pulse. As well as having different meanings to different practitioners, the classic signs of "asphyxia" have been shown to be nonspecific and may be seen in nonasphyxial deaths. These findings are petechiae, cyanosis, congestion, fluidity of the blood, and dilatation of the right side of the heart. The changes are so nonspecific as to be referred to as the "obsolete quintet." This paper traces the development of theories and findings in the English literature over the last two and a half centuries. It is the author's opinion that the use of the term "asphyxia" should now be abandoned as it serves more to confuse than enlighten.